Personality disorder and functioning in major depressive disorder: a nested study within a randomized controlled trial - Kavanagh, Bianca E. (Braz J Psychiatry, 2019)
OBJECTIVE: This study aimed to determine if personality disorder (PD) predicted functional outcomes in patients with major depressive disorder (MDD). METHODS: Data (n=71) from a double-blind, randomized, placebo-controlled 12-week trial assessing the efficacy of 200 mg/day adjunctive minocycline for MDD were examined. PD was measured using the Standardized Assessment of Personality Abbreviated Scale. Outcome measures included Clinical Global Impression – Improvement (CGI-I), Quality of Life Enjoyment and Satisfaction Questionnaire (Q-LES-Q), Social and Occupational Functioning Scale (SOFAS), and Range of Impaired Functioning (RIFT). Analysis of covariance was used to examine the impact of PD (dichotomized factor [≥ 3] or continuous measure) on the outcome measures-treatment group correlation. RESULTS: PD was identified in 69% of the sample. After adjusting for age, sex, and baseline scores for each of the outcome measures, there was no significant difference between participants with and without PD on week 12 scores for any of the outcome measures (all p > 0.14). CONCLUSION: In this secondary analysis of a primary efficacy study, PD was a common comorbidity among those with MDD, but was not a significant predictor of functional outcomes. This study adds to the limited literature on PD in randomized controlled trials for MDD. CLINICAL TRIAL REGISTRATION: ACTRN12612000283875.